Twenty-Five Years of Counting for Nothing: Waring's Critique of National Accounts. Issue 2 (3rd April 2017) - Saunders, Caroline; Dalziel, Paul
ABSTRACT: Marilyn Waring's If Women Counted (1988) shows how national income accounting became infused with the patriarchal values dominant during its post–World War II development. This article revisits Waring's analysis in the light of continued support of gross domestic product as a useful statistic. It explains the historical and personal context for her analysis, emphasizing postwar patriarchal values as well as Waring's experience as a Member of the New Zealand Parliament (1975–84) and her active engagement with women in developed and developing countries. It illustrates the support If Women Counted gives to reformers and recognizes that change has occurred, including provision for satellite accounts in the United Nations System of National Accounts (UNSNA). Nevertheless, the paper concludes that Waring's profound challenge to the central framework of UNSNA will continue as long as the system excludes unpaid household work and impacts on the natural environment from its core statistics.